CAZRI Vishal: New pomegranate variety - Singh, Akath; Meghwal, P R (Indian Horticulture, 2020)
The pomegranate variety, CAZRI Vishal has been released by Central Arid Zone Research Institute, Jodhpur in 2020. It is a cross between Ganesh and Khog varieties. Plants are medium in height and semi vigorous with spreading growth habit. It is an early maturing (120-130 days after anthesis) variety. The hybrid has potential for both internal and export market because of extra large sized fruits of about 350 g and attractive yellowish red colour fruit with very soft seeds. Aril recovery (60%) and juice content (40-45%) is significantly higher than other popular varieties. The TSS is about 17.5-18.6ÂºB with low acidic juice (0.48-0.52%). The fruit yield is about 20-25 kg/plant after five years of planting onward under improved management practices.